UJI DAYA HAMBAT EKSTRAK DAUN SIRSAK (Annona muricata L.) DAN DAUN SIRIH (Piper betle L.) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli - Eka Suci Fitria; Imran Imran; Sulastrianah Sulastrianah (Halu Oleo University, 2014)
Soursop (A. muricata L.) and betel (P. betle L.) are common plants that traditionally used as a medicine. The aims of this study are to determine the Minimum Inhibitory Concentration (MIC) of soursop leaves benefits and betel leaves extract that can inhibit the growth of E. coli one of the cause of diarrhea and the most potentially extract between that plants. Methode of this research used post test control only design and cotrimoxazole (as a control). This study consists of three phases : (1)sample preparation, (2)extraction by maceration with methanol and obtained as much as 14.97 g of leaf extract of A. muricata.L and 2.88 g of P. betle L. after evaporated, (3)MIC using the disc diffusion method. The concentration of each extract are 80,000 ppm, 40,000 ppm, 20,000 ppm, 10,000 ppm, 5000 ppm, 2500 ppm, and 1250 ppm. Ten μL of each extracts was taken and saturated to a paper disc. The results of this study showed that the A. muricata L leaf extract begin to show inhibition at concentration 2500 ppm and P. betle.L is at concentration 5.000 ppm. The conclusion of this study is the MIC of A. muricata L. and P. betle L.leaf extract are 2500 ppm and 5000 ppm sequentially.Key words: A. muricata L., P. betle L., Minimum Inhibitory concentration, E. coli